Commonwealth Heads of Government - The Lusaka Communiqué August 1979. - Commonwealth Secretariat; Commonwealth Organisation ([S.l.] : [s.n.])
These contained the communique issued by the Commonwealth of Heads of States at the end of their meeting in Lusaka, Zambia in August1979.
usc/11/08/2021
Ref.
Keywords: Zambia